Оn the study of behavioral suicide risk factors - Kassen G. А.; Melis, K. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
Abstract. Factors that increase the risk of suicide are: family problems (including the Commission and attempted suicide by family members), frequent cases of psychological pressure from both peers and teachers; school bullying; poor psychological stability (depression, lack of willpower, auto-aggression). Knowledge of these factors is necessary for parents, teachers, school psychologists, social teachers, peers of adolescents in order to timely recognize the danger of suicide and take the necessary measures. Studies of suicide risk factors are relevant due to the fact that they determine the transition from conception and conflict to the implementation of the intention in the form of a suicide act. The article presents differences in perceptions of suicide risk factors and best practices in the study of suicide risk factors, in particular, interesting and advanced studies reflected in the articles of authors from different countries and different periods. It is noted that researchers from foreign countries often do not use mass methods of assessing the situation, preferring a specific sample or more complex methods. As a result of the review of studies to identify suicide risk factors, it is noted that the suicide risk in adolescence has a multifactorial nature, including both psychopathological and psychological mechanisms, as well as environmental and social factors. The growth of auto-destructive behavioral trends at this age, followed by the choice of suicide as a way to solve the problems requires a thorough analysis of the personality of the minor, the sphere of interpersonal relations, features of education and other circumstances for the subsequent formation of strategies of psychosocial prevention and adaptation, as well as the development of forms and methods of psychological and social support for adolescents in the group of suicidal risk. Hermeneutic analysis of criminal case materials within the framework of forensic examination of the mental state of a teenager who committed suicide, as well as access to various sources of information about mental development, personal characteristics, family relationships and situational circumstances preceding suicide are considered as a promising method of suicide risk analysis. It is stated that this will allow to analyze the factors in the aspect of their temporary development, as well as interaction with each other. Key words: suicide, auto-aggression, auto-injury, auto-destructive behavior, self-destructive behavior, suicidal behavior, suicidal risk, Avital activity, behavioral factors of suicidal risk.